Satisfaction of patient users of prosthesis about implant in aesthetic region (Research, Society and Development, 2023)
Introduction: Tooth loss has negative effects directly on the quality of life of patients. With the advent of osseointegrated implants, came the advantages and indisputable good results in masticatory function, aesthetics, comfort and self-esteem of patients, with this, the appearance of the crown, especially in the anterior region of the maxilla, is as important as the health of the implant, and, consequently, should be the focus of such rehabilitation. Objective: to analyze the degree of satisfaction of patients rehabilitated with implant-supported prostheses in aesthetic regions. Methodology: integrative literature review regarding the assessment of satisfaction of patients using implant-supported prostheses in the aesthetic region. The pubmed, scielo and bvs databases were used, with the descriptors: dental prosthesis, dental implant and patient satisfaction. With articles published between 2017 and 2022. Results: Initially, 84 articles were found. After selection, 8 were suitable for the purposes of the study, the information was transferred to the collection instrument. The included articles were presented in a summary table and the analysis of the results was carried out in a descriptive way, presenting the synthesis of the studies through comparisons and highlighting the differences and/or similarities. Conclusion: The type of prosthesis can influence the relevant criteria of degree and satisfaction. Implant prostheses in aesthetic regions provided patients with a better perception of quality of life, stability and comfort, in addition to an improvement in masticatory function after oral rehabilitation.